A Fluid Dynamic Simulation Of A Teniente Converter - M. Rosales (The Minerals, Metals and Materials Society, 1999)
Using the k-e turbulence model, a mathematical fluid dynamics simulation of the flow characteristics in a Teniente converter has been conducted. Two cases were studied: - Transversal sections in the smelting-converting zone; and - A three-dimensional simulation that includes the walls of the reactor The calculations give the velocities field, the gravity waves amplitude, the splashing behaviour, the phase distribution and the shear stress distribution. The latter helps to explain the pattern of refractory lining wear. The calculation includes the approximate shape and dimensions, and the eventual coalescence of bubbles.